Loneliness Pada Lansia dengan Penyakit Kronis di Poli Geriatri - Prajna Sasongko; Isrida Arifiana (Indonesian Journal Publisher, 2026)
This study aimed to explore the dynamics of loneliness among older adults attending a geriatric outpatient clinic in Surabaya and to identify personal, relational, and environmental factors contributing to their experiences. A mixed methods approach with a convergent parallel design was applied. Quantitative data were collected using the UCLA Loneliness Scale Version 3, while qualitative data were obtained through semi-structured interviews and participatory observations. The participants consisted of ten older adults aged 60–85 years who were active patients in the geriatric clinic. Quantitative results indicated that the majority of participants experienced moderate to severe levels of loneliness. Qualitative findings revealed that loneliness was closely related to the loss of meaningful social roles, increased dependency due to chronic illness, limited opportunities for meaningful social interaction, and emotionally distant communication patterns within the family. Participants also described feelings of helplessness, reduced self-worth, and uncertainty about their future, which further intensified their sense of isolation. The integration of quantitative and qualitative findings demonstrates that loneliness among older adults in geriatric care is multidimensional, involving psychological vulnerability, relational disconnection, and environmental constraints within healthcare settings. These findings highlight the importance of incorporating routine psychosocial screening into geriatric services and developing comprehensive interventions that extend beyond medical treatment. Family-based support programs, structured peer-support activities, and community-oriented initiatives are recommended to strengthen social connectedness, promote active engagement, and enhance overall psychological well-being among older adults receiving long-term care.